Raman amplifier performance in pre-amplifier use for optical fiber communication systems - T. Saktioto; S. P. Dewi; R. F. Syahputra; Okfalisa Okfalisa; Syamsudhuha Syamsudhuha (Universitas Ahmad Dahlan, 2019)
The development of telecommunications networks is currently dominated by fiber optics. The fiber optic has become a waveguide medium transmitting information with high frequency bands, high capacity and high speed. An optical amplifier is required to maintain electromagnetic signals when they propagate in far distance. One of the amplifiers, Fiber Raman Amplifiers (FRA) which is the light scattering from the light that comes with the phonon in the lattice of amplification medium produces photons that are coherent with the incoming photons. Many amplifiers are commonly used but the problems not only come from the amplifier but also the component circuit and system. By simulation method, FRA circuit is designed and operated in the form of pre-amplifiers to maintain a better signal from material interference and geometry. The simulation results show that the lowest BER value and the highest Q-factor are found at a distance of 10km depicted by eye diagram.